Development of river data model using object orientation concept - Hashim, Mohamad Ghazali; Majid, Zulkepli; Sipan, Ibrahim @ Atan; Abdul Aziz, Intan Sajidah (UTM, 2003)
River Management is not an easy task to handle. In Malaysia, various agencies are responsible to cater different aspects of the situation. This scenario invokes the need for standard river database that covers multiple users requirement in river management activities. An attempt has been made to tackle the most critical part of the database development process known as data modeling. Various user perspective were taken into consideration in the modeling process based an object-oriented approach. However, the scope of this study is only cover the need of DID departments. This research includes the data model design presented in UML notation for the conceptual design. Followed by explanation of the logical and physical design and several examples of how the data model structure improves the capability of GIS analysis.